PERBEDAAN TINGKAT PEMAHAMAN AKUNTANSI BERDASARKAN LULUSAN (STUDI PADA MAHASISWA PROGAM STUDI AKUNTANSI UNIVERSITAS MUARA BUNGO TAHUN ANGKATAN 2017) - Ronald N Girsang (Yayasan Akrab Pekanbaru, 2019)
This research is to test the level of understanding of accounting for students graduating from Science High School, Social Sciences High School and Accounting Vocational High School. This research was conducted on students of the Accounting Study Program at the Faculty of Economics, Muara Bungo University. Assessment of the level of understanding of accounting is assessed by the level of understanding of assets, liquidity and equity. The results of the study using the Kruskal Wallis test concluded the significant value of the level of understanding of assets, liquidity and equity was less than 0.05 which concluded there was a significant difference in the level of accounting understanding of graduates of Science High School, Social High School and Accounting Vocational School. The results of the Kruskal Wallis mean rank test the level of understanding of asset accounting, liquidity and equity shows that the level of accounting understanding of graduates from accounting Vocational High Schools is higher than those of Science and High School Social Sciences High Schools.